Braiding Indigenous knowledge systems and Western science through co-creation and co-teaching - Jones, Thomas J.; Williams-Jones, Glyn; Nyce, Harry (Frontiers in Earth Science, 2025)
Co-production of Indigenous Knowledge Systems with Western science is increasingly recognised as an important component of education and research. When done correctly, it draws on the strengths of the respective knowledge systems, ensures Indigenous data sovereignty, empowers communities, supports reconciliation, and fosters mutual respect. However, despite these clear benefits and alignment with the United Nations Declaration of the Rights of Indigenous Peoples, few examples, guidance, or frameworks exist, especially in the context of science education. Here, we illustrate how co-designing and co-teaching courses can effectively enhance knowledge systems. We show that students value the weaving of Indigenous Knowledge with science, both within (Westernised) academic settings and during place-based experiential learning. It can deepen connections to Indigenous ways of knowing and provides a source of healing as co-production studies are re-connections to Indigenous history and identity. We conclude by addressing some of the challenges faced and provide some actionable solutions for the global effort needed to decolonise and Indigenise both research and education.